1994
DOI: 10.1161/01.str.25.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the anatomy of the rabbit cervical carotid artery.

Abstract: A model for cerebral ischemia that requires injection of emboli into the internal carotid artery of the rabbit is commonly used. However, in our experience we have found the anatomy of the cervical carotid to be highly variable. If not appreciated, this may result in unexpectedly high variability in the severity of ischemic injury. We undertook this experimental protocol to determine whether it was possible to characterize the anatomy of the rabbit cervical carotid artery. We examined and recorded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 7 publications
(2 reference statements)
0
23
0
Order By: Relevance
“…Ligation of the internal carotid artery, for example, results in doubling of contralateral internal carotid artery flow to maintain total cerebral blood flow. 146,147 With experience, CCA grafting in the rabbit results in a postoperative survival of Ͼ90%, with mortality generally due to anesthetic complications. 140 Cassel et al 140 inserted 2-mm ePTFE grafts (n ϭ 158) in the carotid position and found two distinct patterns of occlusion: a failure rate of 11.2% in the first 2 weeks due to thrombotic occlusion, then patency remained stable out to 16 weeks, beyond which progressive patency loss was seen due to development of IH most marked at the distal anastomosis.…”
Section: Small-animal Models For the Assessment Of Novel Vascular Conmentioning
confidence: 99%
“…Ligation of the internal carotid artery, for example, results in doubling of contralateral internal carotid artery flow to maintain total cerebral blood flow. 146,147 With experience, CCA grafting in the rabbit results in a postoperative survival of Ͼ90%, with mortality generally due to anesthetic complications. 140 Cassel et al 140 inserted 2-mm ePTFE grafts (n ϭ 158) in the carotid position and found two distinct patterns of occlusion: a failure rate of 11.2% in the first 2 weeks due to thrombotic occlusion, then patency remained stable out to 16 weeks, beyond which progressive patency loss was seen due to development of IH most marked at the distal anastomosis.…”
Section: Small-animal Models For the Assessment Of Novel Vascular Conmentioning
confidence: 99%
“…We found that an overly long silicone rubber-coated portion prevented the thread from passing through the foramen caroticum. The success rate in an embolic stroke model was reduced by the failure to recognize that the occipital artery may originate from the ICA, resulting in the misdirection of embolic material into the occipital artery (Lee et al, 1993). Although the occipital artery has been reported to originate from the distal portion of the ICA (Lee et al, 1993), we did not observe this in any of our animals, perhaps because our sample size was too small.…”
Section: Discussionmentioning
confidence: 77%
“…The suboccipital knot enlarges to provide collateral blood flow from subclavian to external carotid artery giving extravascular support to the brain by way of intraorbital ophthalmic anastomoses (2,8). These important anastomotic vascular channels between the extracranial and intracranial arteries are located in three regions along the skull base: the orbital region via the ophthalmic artery between the internal maxillary artery (IMA) and ICA; the petrocavernous region via the inferolateral trunk, the petrous branches of the internal carotid artery, the meningohypophyseal trunk to the carotid artery; and the upper cervical region via the ascending pharyngeal, the occipital, and the ascending and deep cervical arteries to the vertebral artery (17,28,44).…”
Section: █ Discussionmentioning
confidence: 99%